PERANG YANG ADIL MENURUT GEREJA KATOLIK - Mali, Mateus (Jurnal Orientasi Baru, 2017)
Just war theory deals with justification of why and how the war should be fought. Justification can be either theoretical or historical. This essay will primarily deal with ethical justification of war and forms that warfare may or may not take. Methodology employed in this essay will be more historical, to explain how Catholic Church deals with the historical body of rules or agreements that have been applied in various wars across the ages while continuously promoting peace among the people. The goal of this essay is to argue and postulate that war, even an apparent evil, is not always an absolutely wrong option.